Estudos de variáveis de contexto em um episódio verbal - Gomes, Ueliton dos Santos (2017)
The goal of the present work was: to investigate the relations between the independent variables, which in this study were verbal (instructions) and non-verbal (figures and images of objects) contexts and their effects in the dependent variable, which was the descriptive behavior of OBJECTS and ACTIONS in a total verbal episode. We had also a secondary goal: the development of a software for the collect and analysis of data. An experiment was conducted as a systematic replication of the work by Simonassi, Tizo, Gomes e Alvarenga (2010) in order to verify: 1) if verbal and non-verbal contexts exert control over verbal responses in a total verbal episode. This experiment was conducted with ten (10) participants with ages varying from 19 to 25 yeas. Each participant was exposed to 4 different experimental conditions (CONDITIONS 1, 2, 3 and 4) in a singlecase design. During the CONDITIONS 1, 2 and 3 the following instructions was presented: “BURNING THIS TIP HAS BEEN”, being that in the CONDITIONS 2 and 3 the following non-verbal stimuli were presented: MATCHES and a STRING (figures and images) and in the CONDITION 3: MATCHES and a CANDLE (figures and images). In the CONDITION 4 the instruction presented was “BURN IT ON THIS TIP. CALM SIR, STILL ENDING STRUCTURING CLOTHES”. In each condition the participant was asked to write his answers. A categorization of the textual responses as referent to OBJECT or ACTION was used for analysis. We verified a considerable frequency of textual verbal responses that made reference to the related objects (figures/images) and actions. The results were similar to those found by Simonassi & Cols. We concluded that both the verbal (instruction) and non-verbal (objects) contexts, when altered, controlled changes in the participants’ responses across the experimental conditions in a systematic way.